Creating the Conditions for Robust Early Language Development for All--Part Two: Evidence Informed Public Health Framework for Child Language in the Early Years - McKean, Cristina; Reilly, Sheena (International journal of language & communication disorders, 2023)
Background: One of the most significant developmental accomplishments is the emergence of language in early childhood. Whilst this process is effortless for most children, others can face significant hurdles. Identifying, in the early years, which children will go on to have developmental language disorder is, however, fraught with several well-documented challenges. In the preceding paper we described and linked new research evidence about factors that influence language development in the early years, noting that exposure to some may be time sensitive and that these influences cluster together and can accumulate over time. We demonstrated that risk profiles were associated with and characterised low language trajectories, and we considered how this information could be integrated into a concept that moves beyond screening at single time points in the early years. We argue that this evidence might be used to build an improved early years framework for language thereby creating a more equitable surveillance system that does not leave children living in less advantageous circumstances behind. Underpinning this thinking was a bioecological framework that incorporates the social, environmental and family factors in the child's ecosystem known to influence language development in the early years. Aims: To develop a proposal for the design and implementation of an early language public health framework based on current best evidence. Methods: We synthesised the findings from the companion paper (Reilly & McKean 2023) regarding early language trajectories, inequalities and clustering of risks with key public health concepts, relevant intervention evidence and implementation theories to develop a new framework for language surveillance and preventative interventions in the early years. Main Contribution: An evidence informed early language public health framework is presented. Describing in turn (1) essential components; (2) relevant interventions; (3) essential qualities for implementation ((i) probabilistic, (ii) proportionate, (iii) developmental and sustained and (iv) codesigned); (4) system-level structures and (5) processes required to adopt and embed an early language public health framework in an existing Local Government Area's child health surveillance and early prevention-intervention systems. Conclusions: Children's language development influences their life chances across the life course and language difficulties are unfairly distributed across society. Current evidence points to the need for whole systems approaches to early child language and enables a blueprint for such a framework to be described. [For Part 1, see EJ1400160.]